Estudio de factibilidad para la creación de una Academia de Arte dirigida a niños y jóvenes del cantón Latacunga, provincia de Cotopaxi. - Calvopiña Osorio, Oscar Fernando (2021)
Art constitutes the medium, which offers the possibility of stimulating creative abilities in spaces that develop personal talents with experiences in artistic disciplines for cultural rescue. The purpose of this project is to design a feasibility study for the creation of an Arts Academy aimed at children, adolescents and young people in the Latacunga canton, province of Cotopaxi, for the year 2021. The methodology used was a quantitative approach, descriptive basic modality, with a population of 69,194 obtaining a sample of 270 children and young people. The techniques for collecting information was the application of a questionnaire with Likert scale and dichotomous questions. Based on this information, the proposal focused on economic, operational, technical, legal and time analyzes was developed with a (VAN) of $81,593.08 and (IRR) of 22.77%. The results favorably pointed to the feasibility of the proposal, especially from the field of investment with an estimated $172,000, that is, that the project would be attractive to potential future investors. The market study, supply and demand and the applied instrument, gave rise to the need for the opportunity to create the arts academy in the Latacunga area, so that it becomes a training center in the different artistic areas offered, with the purpose of develop potential students. The conclusions highlighted the achievement of the established objectives and the execution of the planned actions, added to making strategic decisions to optimize processes related to this type of project.